A mutual exclusion algorithm for flying Ad Hoc networks. (June 2019) - Khanna, Ashish; Rodrigues, Joel J.P.C.; Gupta, Naman; Swaroop, Abhishek; Gupta, Deepak; Saleem, Kashif; de Albuquerque, Victor Hugo C.
Highlights: The presented exposition introduces mobile resource Mutual exclusion (MRME) problem in FANET. A novel token-based algorithm to solve the MRME problem has also been proposed. The proposed algorithm is fault-tolerant as it handles token-loss. The paper proves the correctness properties of the problem. The static and dynamic performance analysis of the procedure has also been provided. Abstract: Mutual exclusion (ME) is a highly researched problem in distributed computing systems. In the mutual exclusion problem, no two nodes can use critical resource simultaneously. Numerous protocols have been proposed for various types of static as well as mobile distributed systems, namely, Mobile Ad Hoc Networks (MANET), Vehicular Ad Hoc Networks (VANET) and cellular networks. The flying ad hoc networks (FANET) is an interesting variant of distributed systems and, to the best of our knowledge, no protocol exists in the literature for mutual exclusion in FANETs. In FANETs, the critical resource is mounted on an unmanned aerial vehicle (UAV) and user nodes are assumed in the transmission range of the UAV. Ours is the first algorithm to ensure ME in FANETs. The algorithm is token-based and we name it Mobile Resource Mutual Exclusion (MRME) algorithm. Unlike other ad hoc networks, due to swift mobility of nodes as well as resource, the FANETs topology is highly dynamic and fault prone. The MRME algorithm handles it successfully. Further, we present the correctness proof, complexity analysis and simulation results. The worst-case complexity of MRME is O( n ) and synchronization delay is T, where T is message propagation delay.